Brassinolide effects on maize (Zea mays L.) growth and yield under waterlogged conditions. (9th May 2019) - Otie, Victoria; Ping, An; Udo, Idorenyin; Eneji, Egrinya
Abstract: Our aim was to assess if Brassinolide (BR) could ameliorate stress caused by waterlogging on maize. Two BR levels (with and without), two maize varieties [Ikom White (IKW) and Obatanpa-98 (Oba-98)] and three growth stages [control (WLo ), seedling stage (WL1 ), and tasseling stage (WL2 )] were studied under waterlogging lasting 10 days. Maize growth and development were significantly ( p  ≤ .05) reduced by waterlogging stress under WL1 than WL2 . Waterlogging stress at WL1 adversely affected ( p  ≤ .05) the protein and relative water contents. The nitrogen (N) content among the plant partitions (leaves, stems, and grains) were reduced ( p  ≤ .05) at both silking and harvest. The beneficial effect of BR was more pronounced in Oba-98 with higher protein contents, dry matter yield, N-uptake and harvest index than IKW. Oba-98 was also better yielding than IKW. Thus, in a waterlogged soil, treatment of maize plants with BR at WL1 could induce some tolerance.